2021
DOI: 10.1103/physreve.104.064117
|View full text |Cite
|
Sign up to set email alerts
|

Native state of natural proteins optimizes local entropy

Abstract: The differing ability of polypeptide conformations to act as the native state of proteins has long been rationalized in terms of differing kinetic accessibility or thermodynamic stability. Building on the successful applications of physical concepts and sampling algorithms recently introduced in the study of disordered systems, in particular artificial neural networks, we quantitatively explore how well a quantity known as the local entropy describes the native state of model proteins. In lattice models and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…For the 4 most abundant graphs, remarkably, the counts found in natural proteins are larger than for random decoys (red bars in Fig. 5), obtained from the collapse of a protein model in which all atoms interact with the same energy [18].…”
Section: Analysis Of Patterns In Real Proteinsmentioning
confidence: 93%
See 1 more Smart Citation
“…For the 4 most abundant graphs, remarkably, the counts found in natural proteins are larger than for random decoys (red bars in Fig. 5), obtained from the collapse of a protein model in which all atoms interact with the same energy [18].…”
Section: Analysis Of Patterns In Real Proteinsmentioning
confidence: 93%
“…It was suggested that some protein conformations are more 'designable' than others, being able to act as native state of more sequences [11]. Several properties of the native conformation have been associated with an increased designability, including conformational symmetries [12][13][14], abundance of local interactions [15], of returning loops [16], of loops of specified size [17], or a large local entropy [18].…”
Section: Introductionmentioning
confidence: 99%